Pengaruh Kehadiran Media Sosial, Orientasi Pasar Terhadap Kinerja UMKM di Jawa Barat - D. Yadi Heryadi; Dhiana Ekowati; Dhety Chusumastuti (Universitas Nusa Putra, 2023)
Micro, small, and medium enterprises (UMKM) play a crucial role in the economic development of Indonesia, including in West Java. However, many UMKM struggle to compete in a highly competitive market due to resource limitations and limited access to information. This research aims to examine the influence of social media presence and market orientation on the performance of UMKM in West Java. Data were collected from 300 UMKM owners in West Java using a self-administered questionnaire. The results of multiple regression analysis indicate that social media presence and market orientation significantly predict UMKM performance. The findings of this research have important implications for UMKM, policymakers, and government agencies in formulating strategies and policies to support the growth and development of UMKM in West Java and other regions.